The Effectiveness of the International System for Protection of Migrants’ Human Rights - Munguía Salazar, Alex (2017)
Migrant workers’ human rights have been brought to the current scope of public law, and their labor character has been prioritized. This movement for migrant workers’ human rights can be highlighted from the perspective of the entry into force of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, on 1 July 2003. In this document, two international regulatory texts are merged to strengthen the enjoyment of those rights in these groups of migrant workers: ILO Declaration on Fundamental Principles and Rights at Work and the Universal Declaration of Human Rights.